Analysis of The Effect of Years of Schooling, Number of Companies, and Investement on Labor Absorption in West Sumatra Province - wahyuni, syafira (Jurnal Ilmu Ekonomi Terapan, 2019)
The purpose of this research is to find out and analyze the influence of education level, number of companies and investments on employment in West Sumatra Province during the period 1998 - 2017. The type of data used in this study is secondary data. The data used in the form of time series data between the years 1998 - 2017. Data processing using the program Econometric Views (E-views) version 8. The results of this study indicate that during 1998 - 2017, the level of education, number of companies and investment together (simultaneous) has a significant influence on employment. Partially the level of education and investment has a positive and significant effect on employment, and the number of companies has a positive and not significant effect on employment in West Sumatra Province. The coefficient of determination of R-squared shows the number 0.77 which means that the variation of the dependent variable can be explained by the independent variable at 77%.  Keywords: Duration of Education, Number of Companies, Investment, Absorption of Labor JEL: J01; J23